The Definition and Scope of Philosopichal Inquiry - Fauzan Abdillah Syihab; Ramsiah Tasruddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to dissect in depth the nature of philosophy and its scope of study as the foundation of scientific thinking. As the "mother of all sciences," philosophy plays a crucial role in guiding humans to think critically, radically, and systematically amidst the rapid development of science and technology. The method used in this paper is a literature study with a descriptive-analytical approach. The focus of the discussion encompasses the definition of philosophy both etymologically and terminologically, the characteristics of philosophical thinking, and the three main pillars of the philosophy of science: ontology, epistemology, and axiology. The results of the study indicate that philosophical understanding is not merely an abstract theory, but an analytical tool for understanding the nature of truth, the methodology of acquiring knowledge, and the moral responsibility in utilizing science for civilization.